Extracurricular program management at SD Negeri 001 Tembilahan Hulu, Indragiri Hilir Regency - Lia Wahyuni Kanoer; Fadly Azhar; Daviq Chairilsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
The research aims to (a) describe the planning of extracurricular activities at SD Negeri 001 Tembilahan Hulu, Indragiri Hilir Regency, (b) describe the organization of extracurricular activities at SD Negeri 001 Tembilahan Hulu, Indragiri Hilir Regency, (c) describe the implementation of extracurricular activities at SD Negeri 001 Tembilahan Hulu Indragiri Hilir Regency, and (d) describe the supervision of extracurricular activities at SD Negeri 001 Tembilahan Hulu Indragiri Hilir Regency. This research uses a qualitative approach and descriptive methods. Data collection techniques in this research include observation, interviews, taking field notes, observation, and documentation. Based on the research results, it can be concluded that: (a) in designing extracurricular activities at SD Negeri 001 Tembilahan Hulu, it is good, from the results of interviews, the principal holds joint meetings with teachers, then prepares the program, determines the program, appoints supervisor teachers, and determines the activity schedule. Extracurricular, (b) the organization of extracurricular activities is quite good, extracurricular supervisors are appointed directly by the principal, but there is no decree appointing extracurricular supervisors and the extracurricular organizational structure, (c) in the implementation of extracurricular activities at SD Negeri 001 Tembilahan, the implementation is excellent, this can be seen of the students who take part in extracurricular activities can take part in competitions and some get champions/achievements at sub-district and district levels, and (d) the supervision of extracurricular activities at SD Negeri 001 Tembilahan Hulu is quite good, and the principal directly supervises extracurricular activities during the activities. However, written reporting of extracurricular activities from the supervisor to the school principal has not been implemented.